The Spanish Flu pandemic and income distribution in java: lessons from the 1920s - Brata, Aloysius Gunadi; Triandaru, Sigit; Patnasari, Yenny; Setyastuti, Rini; Edi Sutarta, Agustinus; Sukamto, Andreas (Penerbit Universiti Kebangsaan Malaysia, 2022)
COVID-19 pandemic has renewed the debate over economic inequality as well as the relative importance of policies for saving lives vs. protecting livelihoods during times of crisis. This paper therefore offers some insights from economic history through investigating the relationship between the Spanish Flu pandemic and income distribution at the residency level in late colonial Java, Indonesia’s most populous province. In addition, we examine recent inequality trends in Java during COVID-19. Our econometric analysis shows that population fatality during pandemic is negatively associated with economic inequality across 14 residencies. This in turn improved income distribution across residencies in the post-pandemic period in late colonial Java. We also find some evidence that estate land for commercial plantation moderated the re-distributive role of the pandemic. Based on the results, we further discuss the key lessons learned from the Spanish flu for contemporary times, proposing possible causes of increasing inequality due to the COVID-19 pandemic and the importance of protecting citizens in productive age groups, especially those on low incomes. Referring to more recent spatial and temporal trends, we conjecture on the existence of an inequality trap in Java. Although this did not follow the historical pattern evident in late colonial Java, COVID-19 may have at least a scarring effect on residency-level inequality in Java.